Contribution to the flora of Velika plaža and its vicinity in Ulcinj (Montenegro) - Bubanja, Nada; Šinžar-Sekulić, Jasmina; Stevanović, Vladimir (Biologia Serbica, 2019)
This paper presents a taxonomic, ecological and phytogeographic study of the flora of the longest Adriatic beach – Velika plaža, its vicinity, and the island of Ada Bojana in Ulcinj. According to field research and a literature review, there are 962 taxa (species and subspecies) in the area of Velika plaža and the island of Ada Bojana, which represents one fourth of the total Montenegrin flora. The family with the highest number of taxa is Poaceae, while the genus with the largest number of taxa is Euphorbia. Terophytes and hemicryptophytes are dominant in the biological spectrum. Chorological analysis has shown that the Mediterranean-Sub-Mediterranean areal type is the most prominent. There are 12 NATURA 2000 habitats and several associations that belong to a particular type of habitat within the area of Velika plaža and the island of Ada Bojana. Endemic flora is represented by 16 species. Thirty-six relict species have been recorded, as well as 37 species under legal protection within the research area.